If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(7-2x)=14(-1)-8(x-1)
We move all terms to the left:
3(7-2x)-(14(-1)-8(x-1))=0
We add all the numbers together, and all the variables
3(-2x+7)-(14(-1)-8(x-1))=0
We multiply parentheses
-6x-(14(-1)-8(x-1))+21=0
We calculate terms in parentheses: -(14(-1)-8(x-1)), so:We get rid of parentheses
14(-1)-8(x-1)
determiningTheFunctionDomain -8(x-1)+14(-1)
We add all the numbers together, and all the variables
-8(x-1)-14
We multiply parentheses
-8x+8-14
We add all the numbers together, and all the variables
-8x-6
Back to the equation:
-(-8x-6)
-6x+8x+6+21=0
We add all the numbers together, and all the variables
2x+27=0
We move all terms containing x to the left, all other terms to the right
2x=-27
x=-27/2
x=-13+1/2
| (2x+41)+127=180 | | 7x+32=9x-16 | | 3(x-2)+14=-25 | | (3x+9)=(4x-8) | | 15/(-6x)=-4 | | 3x-6=2x+5(3x-2) | | 6k-(7+k)=-(5k+7) | | 1/18w-1/36+1/3w=1/3+w | | X+3=2x-6=x=36 | | 4(6r+3)+2(r=2) | | (2x^2)-12x+1=-11 | | 3|-8x|8=80 | | -3/8t=7/6 | | -3x/2-5=-14 | | 10x=6+7x | | 4u+11=87 | | -7v-24=-2(v+7) | | 11/3+x=43/4 | | 6x+5=3(2x+1 | | 17=v/5+11 | | 4u+11=39 | | 1/4b+4=14 | | -79-7x=-x+95 | | 3x+8x=12 | | 11/4x=23 | | 6(3)-6x=12 | | -5y+30=50 | | -2(t-4)=10 | | 21+3x=3x+18 | | 12+.05x=10+.07x | | 5x-12=-2-5(x-2) | | f(6)=4*6-12 |